ANALISIS KEMAMPUAN RADAR F-16 DAN SUKHOI SU-30 DALAM RANGKA MENDUKUNG KEBERHASILAN MISI OPERASI MILITER - Christine Stephanie Panggabean (2024)
Radar is one of the important components in the avionics equipment of fighter aircraft that plays a vital role in supporting the success of military operation missions. This research analyzes the role of radar systems on Indonesian fighter aircraft to improve the success of military operation missions. Through the technical analysis method, this research highlights the characteristics of radar technology, the comparison of radar on fighter aircraft and the magnitude of obstacles that occur in radar development. The results show that radars on fighter aircraft are capable of performing missions to the point of being able to deal with electronic warfare. In addition, the perceived challenges and influencing aspects in the development of Indonesia's fighter aircraft radar were identified. Keywords : Radar, Fighter Plane, Military Operation Mission Success